International standardization and the Agreement on Technical Barriers to Trade / Andrea Barrios Villarreal. - Barrios Villarreal, Andrea, 1981- (Cambridge University Press, 2018)
International Standardization and the Agreement on Technical Barriers to Trade examines the international standardization system generally, with a specific focus on some of the bodies within this system, along with their rules and procedures. It also examines - and questions - the lack of definition regarding several features related to the system, notably an international standardizing body (ISB) and international standards in the Agreement on Technical Barriers to Trade (TBT). Andrea Barrios Villarreal, who has been involved in standardization activities for more than seven years, provides a unique and in-depth analysis that will be useful to scholars, students and practitioners. This illuminating work is a welcome addition to the international economic law literature and should be read by anyone with an interest in the interaction between trade law and international standardization.